Photopolymer Flexographic Printing Plate Mold for PDMS Microfluidic Manufacture - Peñaherrera Pazmiño, Ana Belén (2025)
Flexographic printing, traditionally used in the packaging industry, has emerged as a promising technology for microfluidic device fabrication due to enabling high resolution and being commercially available at a low cost compared to conventional techniques. This review explores the adaptation of a photopolymer flexographic printing plate mold (FMold) for microfluidics, examining its advantages, challenges, and applications. It offers a state-of-the-art view of the application of FMold for microfluidic systems, which offers a unique opportunity in terms of cost-effectiveness, scalability, and rapid prototyping. Applications are diverse: FMold has enabled the fabrication of microfluidic devices used in enhanced oil recovery to prepare rock-on-a-chip models, droplet generation and storage, suspension cell culture, monoclonal antibody production, complex cell differentiation pattern creation, phage screening, drug screening, cell detection, and cancer stem cell culture. Since its first appearance in 2018, FMold has been utilized in 50 publications in different laboratories around the world. Key advancements, current research trends, and future prospects are discussed to provide a comprehensive overview of this evolving tool.